Natural feeding of the freshwater crab Dilocarcinus pagei Stimpson, 1861 (Decapoda: Trichodactylidae) in the floodplain of the Araguari River, southeastern Brazil - Barboza, Ana Cláudia Garcia; Nogueira, Caio Santos [UNESP]; Bueno, Alessandra Angélica Pádua; Jacobucci, Giuliano Buzá (De Gruyter, 2025)
Freshwater decapods, such as the crabs in the family Trichodactylidae, are key components of benthic food webs, but research on their trophic ecology is limited. This study aimed to investigate variations in the natural diet of the freshwater crab Dilocarcinus pagei in the Araguari River, Brazil. We analyzed demographic groups and seasonal differences in stomach fullness, volume, and frequency of occurrence of various dietary items. Our results revealed that stomach fullness varied among demographic groups, with adult females showing lower levels and juvenile females showing higher levels. Analysis of stomach contents identified 12 types of items, including unidentified animals, detritus, sand, plastic filaments, and molluscs. Juvenile females showed a higher consumption of plant tissue, while only adult males and juveniles showed a consumption of molluscs. Plant tissue and detritus (digested material) were the most frequent items. These findings reveal the feeding habits of D. pagei in the sampling area, highlighting the influence of demographic groups and seasonal variations on their diet, including the consumption of plant tissue, predation on molluscs, and ingestion of microplastics.
Keywords: aquatic invasions; Brachyura; Cerrado; feeding ecology; trophic ecology